UTILIZING CANVAS IN TECHNOLOGY ENHANCED LANGUAGE LEARNING CLASSROOM: A CASE STUDY - Ratu Sarah Pujasari; Ruslan Ruslan (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
The paper aimed at exploring the utility of the Learning Management System in teaching English. It focused on Canvas which as an online learning platform that allowed teachers and students to share content and interact during a course, a web platform that allowed sharing information, viewed student submissions and provided feedback all in one frame. It covered information about the usefulness of this application, Its advantages, and the values of work. This study used a qualitative case study design. The participants were 6 students from the University level who took Technology Enhanced Language Learning Classroom and they used Canvas actively. The data were taken from the document of canvas activities and interview. A thematic analysis showed that there were constructive outcomes based on the students’ viewpoint. The finding contributed to the significance of digital platform, especially LMS, in developing students’ interaction both of the teacher and other students, engaging with the course content and giving positive implications for ELT.